An Exploratory Study of Conflict and Coordination in Interorganizational Service Delivery System - Alter, Catherine (Academy of Management Journal, 1990)
This study examined conflict and coordination in interorganizational service delivery systems. I developed hypotheses relating service and client characteristics to the amount and type of coordination a system used and relating structural variables to the levels of conflict being experienced. Empirical data from 15 interorganizational service delivery systems in two states found evidence supporting four of the five hypotheses. Conflict and coordination had a curvilinear association in these systems, a relationship that was intensified when an interorganizational system was differentiated by function and service mix. In systems that had a dominant core agency, however, it appeared that task integration among workers reduced the level of conflict.